MiR-135 suppresses glycolysis and promotes pancreatic cancer cell adaptation to metabolic stress by targeting phosphofructokinase-1 - Ying Yang (Nature Portfolio, 2019)
Pancreatic ductal adenocarcinoma must adapt to a nutrient-poor microenvironment. Here, the authors show that miR-135 accumulates in response to glutamine deprivation and inhibits aerobic glycolysis by targeting phosphofructokinase-1, thereby redirecting glucose carbon to the TCA cycle and allowing pancreatic cancer cells survival.